Psychological Stress and the Cutaneous Immune Response: Roles of the HPA Axis and the Sympathetic Nervous System in Atopic Dermatitis and Psoriasis - Jessica M. F. Hall; desAnges Cruser; Alan Podawiltz; Diana I. Mummert; Harlan Jones; Mark E. Mummert (Dermatology Research and Practice, 2012)
Psychological stress, an evolutionary adaptation to the fight-or-flight response, triggers a number of physiological responses that can be deleterious under some circumstances. Stress signals activate the hypothalamus-pituitary-adrenal (HPA) axis and the sympathetic nervous system. Elements derived from those systems (e.g., cortisol, catecholamines and neuropeptides) can impact the immune system and possible disease states. Skin provides a first line of defense against many environmental insults. A number of investigations have indicated that the skin is especially sensitive to psychological stress, and experimental evidence shows that the cutaneous innate and adaptive immune systems are affected by stressors. For example, psychological stress has been shown to reduce recovery time of the stratum corneum barrier after its removal (innate immunity) and alters antigen presentation by epidermal Langerhans cells (adaptive immunity). Moreover, psychological stress may trigger or exacerbate immune mediated dermatological disorders. Understanding how the activity of the psyche-nervous -immune system axis impinges on skin diseases may facilitate coordinated treatment strategies between dermatologists and psychiatrists. Herein, we will review the roles of the HPA axis and the sympathetic nervous system on the cutaneous immune response. We will selectively highlight how the interplay between psychological stress and the immune system affects atopic dermatitis and psoriasis.